DAMPAK PER, DER DAN FIRM SIZE TERHADAP PBV PERUSAHAAN PARIWISATA - Amin, M. Irham; Sadikin, Ali; Dalimunthe, Fahmi Roy (CV. Anugerah Duta Perdana, 2024)
For investors, company value is very important, because good company value will attract investors to invest which makes the company's share price increase. In this study, company value is proxied by Price Book Value (PBV) while the independent variables use investment decisions, funding decisions, and company size. The research population used the tourism and recreation sub-sector as many as 41 companies for the 2016-2020 period while the sample was 15 with the porpusive sampling method. The result is that the Price Earning Ratio (PER) has a positive and insignificant effect on the value of companies in the tourism and recreation sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period. Debt to Equity Ratio (DER) has a positive and insignificant effect on the value of companies in the tourism and recreation sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period. Company Size has a negative and insignificant effect on the value of tourism and recreation sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period.